Visualization of the dolphin kicking wake using 2C-PIV technique - Miwa, T.; Matsuuchi, K.; Sakakibara, J.; Muramatsu, Y.; Nomura, T. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The aim of this study was to visualize and to analyze the wake of a swimmer`s dolphin kick in a horizontal and a vertical (sagittal) plane using two-component PIV (2C-PIV) technique. PIV allows us to visualize the unsteady flow field instantaneously and to estimate the fluid force. One trained male swimmer was instructed to maintain a swimming position with dolphin kicking in a swimming flume. Unsteady flow fields of dolphin kicking wake in a sagittal and a vertical plane was measured by 2C-PIV. Results of both horizontal and vertical planes showed the pairs of vortices and jet flow between them especially after a downward kicking motion. The direction of the jet flow was mostly oriented to backward. Therefore, it was plausible that the dolphin kicking motion performed in this study generated a propulsive force by generating the vortex pair and the jet flow as a reaction force.